2014
DOI: 10.1097/fpc.0000000000000061
|View full text |Cite
|
Sign up to set email alerts
|

Cancer patients’ acceptance, understanding, and willingness-to-pay for pharmacogenomic testing

Abstract: Among cancer patients willing to undergo chemotherapy, almost all wanted pharmacogenomic testing and were willing-to-pay for it, waiting several weeks for results. Although patients had a strong desire to be involved in decision-making on pharmacogenomic testing, a considerable proportion lacked the necessary knowledge to make informed choices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
61
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 31 publications
4
61
1
Order By: Relevance
“…Despite their high readiness to adopt genomic technologies and desire to be involved in test-related decision-making, self-perceived deficiencies in understanding represent a barrier to test utilisation (Cuffe et al, 2014;Issa, Tufail, Hutchinson, Tenorio, & Baliga, 2009). Despite their high readiness to adopt genomic technologies and desire to be involved in test-related decision-making, self-perceived deficiencies in understanding represent a barrier to test utilisation (Cuffe et al, 2014;Issa, Tufail, Hutchinson, Tenorio, & Baliga, 2009).…”
mentioning
confidence: 99%
“…Despite their high readiness to adopt genomic technologies and desire to be involved in test-related decision-making, self-perceived deficiencies in understanding represent a barrier to test utilisation (Cuffe et al, 2014;Issa, Tufail, Hutchinson, Tenorio, & Baliga, 2009). Despite their high readiness to adopt genomic technologies and desire to be involved in test-related decision-making, self-perceived deficiencies in understanding represent a barrier to test utilisation (Cuffe et al, 2014;Issa, Tufail, Hutchinson, Tenorio, & Baliga, 2009).…”
mentioning
confidence: 99%
“…In contrast to surveys within the general population, surveys of individuals with specific diseases (or of those at risk for specific diseases) revealed that these individuals are willing to pay for genetic testing that identifies benefit from treatment, changes in treatment or level of risk and is influenced by household income (those with higher income willing to pay more) and understanding of genetic information (Supplementary Online Table) [27,2931]. Research by Eden et al and Cuffe et al found that prior knowledge or a better understanding of the condition or genetic testing led to higher WTP [27,29].…”
Section: Discussionmentioning
confidence: 99%
“…Research by Eden et al and Cuffe et al found that prior knowledge or a better understanding of the condition or genetic testing led to higher WTP [27,29]. Concern about disease may also play an important role.…”
Section: Discussionmentioning
confidence: 99%
“…11 The potential psychological impacts, along with concerns regarding family planning, fertility, lifestyle choices and health management, 5,12 indicate individualized management and genetic counseling should remain a priority. 3,10 A large body of research has investigated public [13][14][15][16][17] and patient 1,3,[18][19][20][21][22] perceptions of genetic testing, and reported that despite low levels of understanding, perceived benefits outweigh the risks. Patients' most highly-rated benefits include increased knowledge, better outcomes, and more effective prevention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In particular, much attention is focused on personalized or precision medicine, the use of molecular tools to individualize healthcare through genetic testing, whole genome sequencing, exome, or transcriptone sequencing. 2 In childhood cancer care, most survivors are currently given information about their risk of developing long-term side-effects from their cancer or treatment (known as 'late effects') which is not specific to their genetic profile.…”
Section: Introductionmentioning
confidence: 99%